Analyzing and Enhancing Dynamic Threshold Policy of Data Center Switches - Shan, Danfeng; Jiang, Wanchun; Ren, Fengyuan (IEEE transactions on parallel and distributed systems, 2017)
Today's data center switches usually employ on-chip shared memory; buffer management policy in them is essential to ensure fair sharing of memory among all ports. Among various polices, Dynamic Threshold (DT) policy is widely used by switch vendors. Meanwhile, in data centers, distributed applications such as MapReduce often introduce micro-burst traffic into network and the packet dropping caused by micro-burst usually leads to serious performance degradation. When micro-burst traffic arrives at switches, DT is unable to fully utilize the buffer to absorb it. Therefore, in this paper, we theoretically deduce the sufficient conditions for packet dropping caused by micro-burst traffic, and quantitatively estimate the free buffer size when packets are dropped. The results show that the free buffer size can be very large when the number of overloaded ports is small. What's worse, to ensure fair sharing of memory among output ports, packets from micro-burst traffic may be dropped even when the traffic size is much smaller than the buffer size. In light of these results, we propose the Enhanced Dynamic Threshold (EDT) policy, which can alleviate packet dropping caused by micro-burst traffic through fully utilizing the switch buffer and temporarily relaxing the fairness constraint. The simulation results show that EDT can absorb more micro-burst traffic than DT.